Effect of tailwater on jet flipping downstream of a sluice gate - Fong, Xi Ning (2014)
Scour has been a problem associated with the operation of hydraulic structures since their debut in the 19th century. This is because scour endanger the stability of hydraulic structure and human safety. Since then, scientists and researchers have been identifying the types of scours and the conditions behind their formation in order to minimize instability. This report aims to study the situations and conditions of scour formation under a sluice gate for two types of uniform sands with median size of 3.19 mm and 1.62 mm respectively. The objective is to study the effect of tailwater depths on the scour formation.